Functional characteristics of circulating granulocytes in severe congenital neutropenia caused by ELANE mutations - Qiao Liu; Martina Sundqvist; Wenyan Li; André Holdfeldt; Liang Zhang; Lena Björkman; Johan Bylund; Claes Dahlgren; Cai Wang; Xiaodong Zhao; Huamei Forsman (BMC, 2019)
Abstract Background Neutrophils and eosinophils are multifunctional granulocytes derived from common myelocytic-committed progenitor cells. Severe congenital neutropenia 1 (SCN1) caused by ELANE mutations is a rare disease characterized by very low numbers of circulating neutrophils. Little is known about the functional characteristics of the SCN1 granulocytes, except that eosinophilia has been noticed in both bone marrow and peripheral blood. In this study, we profiled the number and function of granulocytes in patients suffering from SCN1. Methods Nine patients diagnosed with SCN1 were enrolled in this study and absolute counts of eosinophils and neutrophils from bone marrow aspirates and peripheral blood samples were analysed. In addition, Ficoll-Paque enriched granulocytes from patients and healthy controls were analysed for specific eosinophil and neutrophil markers using flow cytometry and for NADPH-oxidase activity-profile by chemiluminescence. Results Our data demonstrate a skewed granulocyte population in SCN1 patients dominated by eosinophils in both bone marrow and peripheral blood. The latter was detected only by blood smear examination, but not by automated blood analysers. Furthermore, we show that the SCN1 eosinophils exerted normal production of reactive oxygen species generated by the NADPH-oxidase, however the response was profoundly different from that of healthy control neutrophils. Conclusions SCN1 patients with ELANE mutations suffer from neutropenia yet display eosinophilia in the bone marrow and blood, as revealed by smear examination but not by automatic blood analysers. The SCN1 eosinophils are functionally normal regarding production of reactive oxygen species (ROS). However, the ROS profile produced by eosinophils differs drastically from that of neutrophils isolated from the same blood donor, implying that the eosinophilia in SCN1 cannot compensate for the loss of neutrophils regarding ROS-mediated functions.